Innovative Methods in Logistics and Supply Chain Management: Current Issues and Emerging Practices - Thorsten Blecker; Wolfgang Kersten; Christian M. Ringle (epubli GmbH, 2014)
Innovation is increasingly considered as an enabler of business competitive advantage. More and more organizations focus on satisfying their consumer's demand of innovative and qualitative products and services by applying both technology-supported and non technology-supported innovative methods in their supply chain practices. Due to its very characteristic i.e. novelty, innovation is double-edged sword; capturing value from innovative methods in supply chain practices has been one of the important topics among practitioners as well as researchers of the field. This volume, edited by Thorsten Blecker, Wolfgang Kersten and Christian M. Ringle, provides valuable insights into: Innovative and technology-based solutions, Supply chain security management and Cooperation and performance practices in supply chain management.
urn:nbn:de:gbv:830-tubdok-12911; https://econpapers.repec.org/RePEc:zbw:hiclch:209223; https://econpapers.repec.org/RePEc:zbw:hiclch:209224; https://econpapers.repec.org/RePEc:zbw:hiclch:209225; https://econpapers.repec.org/RePEc:zbw:hiclch:209226; https://econpapers.repec.org/RePEc:zbw:hiclch:209227; https://econpapers.repec.org/RePEc:zbw:hiclch:209228; https://econpapers.repec.org/RePEc:zbw:hiclch:209229; https://econpapers.repec.org/RePEc:zbw:hiclch:209230; https://econpapers.repec.org/RePEc:zbw:hiclch:209231; https://econpapers.repec.org/RePEc:zbw:hiclch:209232; https://econpapers.repec.org/RePEc:zbw:hiclch:209233; https://econpapers.repec.org/RePEc:zbw:hiclch:209234; https://econpapers.repec.org/RePEc:zbw:hiclch:209235; https://econpapers.repec.org/RePEc:zbw:hiclch:209236; https://econpapers.repec.org/RePEc:zbw:hiclch:209237; https://econpapers.repec.org/RePEc:zbw:hiclch:209238; https://econpapers.repec.org/RePEc:zbw:hiclch:209239; https://econpapers.repec.org/RePEc:zbw:hiclch:209240; https://econpapers.repec.org/RePEc:zbw:hiclch:209241; https://econpapers.repec.org/RePEc:zbw:hiclch:209242; https://econpapers.repec.org/RePEc:zbw:hiclch:209243; https://econpapers.repec.org/RePEc:zbw:hiclch:209244; https://econpapers.repec.org/RePEc:zbw:hiclch:209245; https://econpapers.repec.org/RePEc:zbw:hiclch:209246; https://econpapers.repec.org/RePEc:zbw:hiclch:209247; https://econpapers.repec.org/RePEc:zbw:hiclch:209248
Keywords: 650; Logistics; Supply Chain Management; Performance Management; Supply Chain Security